The Great Whale River ecosystem: ecology of a subarctic river and its receiving waters in coastal Hudson Bay, Canada. Issue 3 (2nd October 2021) - Nozais, Christian; Vincent, Warwick F.; Belzile, Claude; Gosselin, Michel; Blais, Marie-Amélie; Canário, João; Archambault, Philippe
ABSTRACT: The Great Whale River in subarctic Quebec, Canada, is one of the main freshwater inflows to Hudson Bay. This region is experiencing rapid climate change, with pronounced impacts on the cryosphere, and ongoing socio-economic development that may accelerate with future road and shipping links. This review integrates information available to date on the Great Whale River ecosystem, which we define as the river and its watershed, its source lakes and streams, and the river mouth environment and beyond the shoreline in southeastern Hudson Bay. Our aim was to define the current state of this ecosystem as a baseline for ongoing observations, with emphasis on (1) the distribution of water masses, optical characteristics, freshwater discharge, and ice cover; (2) concentrations and fluxes of carbon, nutrients, and contaminants; (3) abundance, production and diversity of the organisms associated with the sea ice ecosystem; (4) plankton abundance, biomass, production, and assemblages; (5) benthic abundance and diversity; (6) fish abundance, diversity and population dynamics; (7) marine mammal biology; and (8) global change impacts on freshwater and marine habitats. This synthesis provides a first step towards the integrated management of the Great Whale River ecosystem, and for similar freshwater-marine systems in the subarctic region.